How do pre-service mathematics teachers resolve proportion tasks? Focus on the problem-solving strategy - Sugiarni, Rani; Herman, Tatang; Suryadi, Didi; Prabawanto, Sufyani (Beta: Jurnal Tadris Matematika, 2024)
[English]: Problem-solving for proportion tasks has not fully incorporated various appropriate strategies. This study aimed to identify and analyze the strategy used by pre-service mathematics teachers in solving proportion problems. This research used a qualitative method with a phenomenological design. The participants of this study were 29 pre-service mathematics teachers who had learned the concept of proportion. Data were collected using tests, interviews, observation, and document study techniques. Data were analyzed in the following stages: data collection, data reduction, data review, and conclusions. The results obtained were in the form of a description of the techniques used in solving proportion tasks. The pre-service mathematics teachers were mostly employing the cross-product strategy in solving proportion tasks. The results of this study can be used as a framework to develop the hypothetical learning trajectories of proportion material for pre-service mathematics teachers in the future. [Bahasa]: Penyelesaian soal perbandingan belum sepenuhnya memasukkan berbagai strategi yang tepat. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis strategi yang digunakan calon guru matematika dalam menyelesaikan masalah perbandingan. Penelitian ini menggunakan metode kualitatif dengan desain fenomenologis. Partisipan penelitian ini berjumlah 29 mahasiswa calon guru matematika yang telah mempelajari konsep perbandingan. Data dikumpulkan menggunakan teknik tes, wawancara, observasi, dan studi dokumen. Data dianalisis secara bertahap, mulai dari pengumpulan data, reduksi data, penelaahan data, dan penarikan kesimpulan. Hasil yang diperoleh berupa uraian tentang teknik-teknik yang digunakan dalam menyelesaikan tugas terkait materi perbandingan. Mahasiswa calon guru matematika sebagian besar menggunakan strategi cross-product dalam menyelesaikan tugas perbandingan. Hasil penelitian ini dapat digunakan sebagai kerangka kerja untuk mengembangkan hypothetical learning trajectory dari materi perbandingan untuk mahasiswa calon guru matematika di masa yang akan datang.